Energy-absorbing structures with multi-material topology optimization considering large deformation - Daiki WATANABE; Masatoshi SHIMODA (Nihon Kikai Gakkai ronbunshu)
Future vehicle design will require lightweight, crashworthy, and stiffness, yet it will balance these requirements. A promising approach, multi-material topology optimization, can reasonably place solid materials with different mechanical properties within the structure. In this study, we propose a multi-material topology optimization approach that maximizes energy absorption performance to achieve better results in large deformation scenarios. Unlike conventional methods that assume constant external loads, the objective function of this study is defined as that which maximizes the corresponding reaction force for fixed displacement. The proposed method is demonstrated and discussed through several numerical examples.